Drug resistant epilepsy as the consequence of inadequate control of type 1 diabetes - Ewa M. Sokolewicz; Kamil Dzwilewski; Natalia Omieczyńska; Marta Zawadzka; Maria Mazurkiewicz-Bełdzińska (Pediatric Endocrinology, Diabetes and Metabolism)
Hypoglycemic encephalopathy (HE) is a type of encephalopathy resulting from extremely low blood glucose level. Symptoms are not specific and can be misdiagnosed very often. It can occur during deep and/or prolonged hypoglycemia, which may be a result of inadequately controlled diabetes. Here, we report a case of an 11-year old male patient diagnosed with type 1 diabetes mellitus treated with the use of insulin pump who was admitted to the Pediatric Neurology Department because of multiple incidents of seizures. Boy was found unconscious by his mother. The blood glucose level on the glucometer was 35 mg/dl. It turned out that the reason of hypoglycemia was inadequate insulin dosing. He was given intravenous glucose by the ambulance service without improvement in the state of consciousness. Brain MRI revealed in both cerebral hemispheres, symmetrically, elevated white matter signal, mainly in the subcortex and cortex of the frontal and occipital and parietal lobes with features of diffusion restriction. EEG revealed generalized slow brain activity, without obvious epileptiform. Boy was provided with a variety of antiepileptic drugs. Unfortunately, none of them yielded with satisfactory results so far and the patient is still suffering from drug-resistant epilepsy. In conclusion, glucose is one of the key metabolic agents for the proper brain function and any imbalances in its blood level may impair the neuronal computation. Thus, it is extremely important, especially among diabetic patients, to control glucose blood level and avoid any disturbances, as they may lead to severe consequences, such as HE and drug-resistant epilepsy.